Q-angle static or dynamic measurements, which is the best choice for patellofemoral pain? - Silva, Danilo de Oliveira [UNESP]; Briani, Ronaldo Valdir [UNESP]; Pazzinatto, Marcella Ferraz [UNESP]; Gonçalves, Ana Valéria; Ferrari, Deisi; Aragão, Fernando Amâncio; Azevedo, Fábio Mícolis de [UNESP] (Elsevier B. V., 2015)
The elevated Q-angle seems to be one of the most suggested factors contributing to patellofemoral pain. Females with patellofemoral pain are often evaluated through static clinical tests in clinical practice. However, the adaptations seem to appear more frequently in dynamic conditions. Performing static vs. dynamic evaluations of widely used measures would add to the knowledge in this area. Therefore, the aim of this study was to determine the reliability and discriminatory capability of three Q-angle measurements: a static clinical test, peak dynamic knee valgus during stair ascent and a static measurement using a three-dimensional system. Twenty-nine females with patellofemoral pain and twenty-five pain-free females underwent clinical Q-angle measurement and static and dynamic knee valgus measurements during stair ascent, using a three-dimensional system. All measurements were obtained and comparisons between groups, reliability and discriminatory capability were calculated. Peak dynamic knee valgus was found to be greater in the patellofemoral pain group. On the other hand, no significant effects were found for static knee valgus or clinical Q-angle measurements between groups. The dynamic variable demonstrated the best discriminatory capability. Low values of reliability were found for clinical Q-angle, in contrast to the high values found for the three-dimensional system measurements. Based on our findings, avoiding or correcting dynamic knee valgus during stair ascent may be an important component of rehabilitation programs in females with patellofemoral pain who demonstrate excessive dynamic knee valgus. Q-angle static measurements were not different between groups and presented poor values of discriminatory capability.
Keywords: Patellofemoral joint; Quadriceps angle (Q-angle); Lateral patellar maltracking; Kinematic; Anterior knee pain